Differential Level of RXFP3 Expression in Dopaminergic Neurons Within the Arcuate Nucleus, Dorsomedial Hypothalamus and Ventral Tegmental Area of RXFP3-Cre/tdTomato Mice - Voglsanger, Lara M.; Read, Justin; Ch’ng, Sarah S.; Zhang, Cary; Eraslan, Izel M.; Gray, Laura; Rivera, Leni R.; Hamilton, Lee D.; Williams, Richard; Gundlach, Andrew L.; Smith, Craig M. (Frontiers in Neuroscience, 2021)
RXFP3 (relaxin-family peptide 3 receptor) is the cognate G-protein-coupled receptor for the neuropeptide, relaxin-3. RXFP3 is expressed widely throughout the brain, including the hypothalamus, where it has been shown to modulate feeding behaviour and neuroendocrine activity in rodents. In order to better characterise potential mechanisms that underlie these effects, this study determined whether RXFP3 is expressed by dopaminergic neurons within the arcuate nucleus (ARC) and dorsomedial hypothalamus (DMH), in addition to the ventral tegmental area (VTA). Neurons that express RXFP3 were visualised in coronal brain sections from RXFP3-Cre/tdTomato mice, which express the tdTomato fluorophore within RXFP3-positive cells, and dopaminergic neurons in these areas were visualised by simultaneous immunohistochemical detection of tyrosine hydroxylase-immunoreactivity (TH-IR). Approximately 20% of ARC neurons containing TH-IR coexpressed tdTomato fluorescence, suggesting that RXFP3 can influence the dopamine pathway from the ARC to the pituitary gland that controls prolactin release. The ability of prolactin to reduce leptin sensitivity and increase food consumption therefore represents a potential mechanism by which RXFP3 activation mediates its demonstrated effects on feeding. A similar proportion of DMH neurons containing TH-IR expressed RXFP3-related tdTomato fluorescence, consistent with a possible RXFP3-mediated regulation of stress and neuroendocrine circuits. In contrast, RXFP3 was barely detected within the VTA. Strong tdTomato fluorescence was also detected within the pars tuberalis of the pituitary gland, also consistent with possible regulation of prolactin. Together, these findings identify potential hypothalamic mechanisms through which RXFP3 influences neuroendocrine control of metabolism, and further highlight the therapeutic potential of targeting this receptor in feeding-related disorders.